Bergenia crassifolia plants growing at the Tromsø Arctic-Alpine Botanical Garden - Campbell, Sandy (2024)
These hardy plants were in bloom in early June at the Tromsø Arctic-Alpine Botanical Garden (69° 40' 36.48" N). Bergenia crassifolia is native to Kazakhstan and western Siberia to Mongolia, the Russian Far East, and Korea.